2018
DOI: 10.1080/23802359.2018.1424577
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of Asarum sieboldii Miq. (Aristolochiaceae), a medicinal plant in Korea

Abstract: Asarum sieboldii is a medicinal plant belonging to the Aristolochiaceae family. In this study, complete chloroplast genome sequence of A. sieboldii was characterized through de novo assembly with next generation sequencing data. The chloroplast genome is 193,356 bp long and has the stereotypical tripartite organization consisting of large single copy region and a pair of inverted repeats. The genome contains 78 protein-coding genes, 30 rRNA genes, and 4 tRNA genes. Phylogenetic analysis revealed that A. siebol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…Syntenically disrupted and otherwise divergent plastomes have been reported in some American Asarum species, which were suggested as contigs of the sequence, but not a completely circularized map [42]. The structural change was supported based on the complete plastome map of A. sieboldii, a member of the section Asiasarum [43]. However, it remains unclear whether changes in the IRs boundary would be present throughout the section.…”
Section: Introductionmentioning
confidence: 93%
“…Syntenically disrupted and otherwise divergent plastomes have been reported in some American Asarum species, which were suggested as contigs of the sequence, but not a completely circularized map [42]. The structural change was supported based on the complete plastome map of A. sieboldii, a member of the section Asiasarum [43]. However, it remains unclear whether changes in the IRs boundary would be present throughout the section.…”
Section: Introductionmentioning
confidence: 93%
“…The average chloroplast genome (plastome) size of land plants is 151 kb, with most species ranging from 130–170 kb in length, and the average GC content is 36.3% (NCBI database, 4,281 land plant plastomes, March 17, 2020) ( Supplementary Table 1 ). However, previous studies documented that the plastome size of some lineages was extremely enlarged ( Chumley et al, 2006 ; Kim et al, 2015 ; Blazier et al, 2016 ; Weng et al, 2017 ; Lim et al, 2018 ; Gruzdev et al, 2019 ; Li H. et al, 2020 ). The largest chloroplast genome of angiosperm is Pelargonium transvaalense (242, 575 bp), with the inverted repeat (IR) region of the species expanding to 87,724 bp ( Weng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 96%
“…However, extensive studies have also found that atypical genome structures and gene contents frequently occur among several distantly related families [20]. Among fully photosynthetic angiosperms, the variation in their genome structures is largely attributable to the expansion and contraction of IRs, the most extreme examples being the complete deletion of one copy (e.g., the IR-lacking clade of Fabaceae) and the expansion to an entire single-copy region shown from the genus Asarum L. within Aristolochiaceae [2122]. Genome rearrangements via large inversions and reductions in gene numbers have been reported from Campanulaceae [2324], Geraniaceae [2527], and Oleaceae [28].…”
Section: Introductionmentioning
confidence: 99%